2018
DOI: 10.1007/s00442-018-4081-y
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic differences in soil biota promote invasive grass response to nutrient addition relative to co-occurring species despite lack of belowground enemy release

Abstract: Multiple plant species invasions and increases in nutrient availability are pervasive drivers of global environmental change that often co-occur. Many plant invasion studies, however, focus on single-species or single-mechanism invasions, risking an oversimplification of a multifaceted process. Here, we test how biogeographic differences in soil biota, such as belowground enemy release, interact with increases in nutrient availability to influence invasive plant growth. We conducted a greenhouse experiment usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…The majority of studies describing underlying mechanisms for successful invasion have focused on aboverather than belowground processes, however accumulating evidence suggests soil organisms may be important regulators of plant invasions [37][38][39][40] . Although many invasive plants are mycotrophic (~ 82% 41 , and fungal associations have been shown to both facilitate and hinder invasion success [42][43][44][45][46][47][48][49][50] , the role of AM mycelial networks in the invasion process has not been determined. Further, information on the role of mycorrhizae on invasive plant success is available for only a small number of plant species at this time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies describing underlying mechanisms for successful invasion have focused on aboverather than belowground processes, however accumulating evidence suggests soil organisms may be important regulators of plant invasions [37][38][39][40] . Although many invasive plants are mycotrophic (~ 82% 41 , and fungal associations have been shown to both facilitate and hinder invasion success [42][43][44][45][46][47][48][49][50] , the role of AM mycelial networks in the invasion process has not been determined. Further, information on the role of mycorrhizae on invasive plant success is available for only a small number of plant species at this time.…”
mentioning
confidence: 99%
“…By doing so, invasive plants strongly affect mycorrhizal symbiosis of native mycorrhizal plants, often reducing native plant competitiveness 46,53 . (ii) The 'enhanced mutualist hypothesis' 52 indicates invasive plants receive greater benefit from the symbiosis than native plants, altering native AM fungal communities and increasing invasive species competitiveness 50,52,54,55 . Therefore, invasive plants in their new range may parasitize local CMNs, deriving disproportionally large benefits compared to their symbiotic costs at the expense of competing native plants.…”
mentioning
confidence: 99%
“…This corresponds to the fact that more than 80% of neophyte species are mycotrophic (Cronk and Fuller 2013). Several studies have already confirmed the significant role of AMF in the invasions of several plant species (Broadbent et al 2018;Bunn et al 2015;Gucwa-Przepiora et al 2016;Nunez and Dickie 2014;Richardson et al 2000).…”
Section: Introductionmentioning
confidence: 88%
“…而养分、光照、温度等环境因素也会影响入侵植物和本地植物之间的竞争(Suding et al, 2004;Bradley et al, 2010;Verlinden et al, 2014;Broadbent et al, 2018)。 …”
unclassified